The Proinflammatory Cytokines IL-18, IL-21, and IFN-γ Differentially Regulate Liver Inflammation and Anti-Mitochondrial Antibody Level in a Murine Model of Primary Biliary Cholangitis. (7th March 2022) - Xu, Ya-Fei; Yao, Yuan; Ma, Min; Yang, Shu-Han; Jiang, Peng; Wang, Jinjun; Tsuneyama, Koichi; Wang, Chan; Liu, Xiangdong; Li, Liang; Lian, Zhe-Xiong
Abstract : Primary biliary cholangitis (PBC) is a cholestatic liver disease primarily featured by autoimmune-mediated damage of intrahepatic small- and medium-sized bile ducts. Elevated serum proinflammatory cytokines, serum anti-mitochondrial antibodies (AMAs), liver inflammation, and fibrosis are also hallmarks of PBC disease. However, whether the elevated proinflammatory cytokines play a role in autoimmune cholangitis remains unknown. Herein, we utilized the p40 -/- IL-2R α -/- PBC mouse model to investigate the roles of proinflammatory cytokines IL-18, IL-21, and IFN- γ in the onset and progression of PBC. IL-18 -/-, IFN- γ -/-, and IL-21 -/- mice were crossed with p40 -/- IL-2Ra +/- mice, respectively, to produce corresponding cytokine-deficient PBC models. Autoantibody level, liver inflammation, and bile duct injury were analyzed. We found that livers from p40 -/- IL-2R α -/- mice exhibit similar transcriptomic characters of PBC patients. In p40 -/- IL-2R α -/- mice, deletion of IL-18 has no remarkable effect on disease progression, while deletion of IL-21 indicates that it is necessary for AMA production but independent of liver inflammation and cholangitis. IFN- γ is responsible for both AMA production and liver inflammation in our model. Our results demonstrate that different proinflammatory cytokines can regulate different effector functions in PBC pathogenesis and need to be considered in PBC treatment.